DEVELOPMENT OF DOMESTIC PUBLIC PROCUREMENT IN THE SHADOW OF CRISIS SITUATIONS OF PAST YEARS - Boros, Anita; Kovács, László (Economica, 2022)
In the economic sense, the COVID-19 crisis has resulted in a fast-moving, rebounding crisis. In the course of our research, we looked for the answer to what results the pandemic crisis brought about from a public procurement point of view, and what peculiarities can be identified as a result of the current Russian-Ukrainian conflict and the energy crisis. Our basic hypothesis is that the pandemic crisis situation had a less negative impact on the Hungarian public procurement market, however, the Russian-Ukrainian conflict and the energy crisis result in a much more complex economic situation, so their impact is likely to be more prolonged.